MENYIBAK CITRAAN DALAM KUMPULAN PUISI "KOPI KEHIDUPAN" CIPTAAN MR. SAE: ANALISIS PENDEKATAN OBJEKTIF YANG MENGGUGAH - Su'aidi Hariyanto (Jurnal Membaca (Bahasa dan Sastra Indonesia), 2026)
This study aims to describe the types of imagery in the poetry collection Kopi Kehidupan. The background of this study emphasizes the tendency of poets to use complex and abstract language, resulting in a lack of clarity in meaning. This study uses a qualitative approach and descriptive method. The data source is the book Kopi Kehidupan, collected through documentation techniques by reading, marking, and grouping. Data analysis follows the Miles and Huberman technique, which includes data reduction, data presentation, conclusion drawing, and time triangulation to protect authenticity. The results of the study show six types of imagery with 36 quotations, including 9 quotations of visual imagery, 7 auditory, 3 tactile, 15 movement, 1 olfactory, and 1 gustatory. All of the imagery embellished the poems and reinforced the moral messages and religious diction embedded in Mr. Sae's poems, which contain values of struggle.